Modified dome osteotomy and anterior locking plate fixation for distal radius variant of Madelung deformity: a retrospective study. Issue 2 (1st April 2022) - Leti Acciaro, Andrea; Garagnani, Lorenzo; Lando, Mario; Lana, Debora; Sartini, Silvana; Adani, Roberto
Abstract: Purpose: Dome osteotomy of the distal radius with Vickers ligament release is an established method of treatment for Madelung deformity. Many different surgical procedures have been proposed in literature but techniques, patient inclusion and efficacy evaluations are heterogeneous. Materials and methods: A retrospective review of children affected by 'distal radius' Madelung deformity and treated with a standardized surgical procedure (modified reverse dome osteotomy of the distal radius and volar fixation with a small locking plate) between 2010 and 2018 at a single center was performed. The technique used in this study, reversing the shape of the classical dome osteotomy, allowed for an improved three-planar correction of the distal radial epiphysis and volar plate fixation allowed for an increased stability and reduced soft tissue morbidity. A structured follow-up including a prompt post-operative rehabilitation program (without wrist immobilization) was established. Pain relief, functional outcome and cosmetic appearance were assessed with a structured clinical assessment, DASH Score and radiographic assessment, accordingly. Results: A total of 15 wrists in 13 children (12 females, mean age of 15.6 years, range 11–19) were included. The mean follow-up time was 3.8 years. Bone union and pain relief were obtained in all cases. Improvement in the range of motion was detected in extension, supination and flexion of the wrist. Radial inclination was increased by 15.3° and lunate subsidence by 4.1 mm. Conclusions: The use of volar fixation with a small locking plate and immediate post-operative rehabilitation for reverse dome osteotomy of the distal radius in pediatric patients affected by 'distal radius' Madelung's deformity is stable and effective.